Can brain impairment be detected by in utero behavioural patterns?. Issue 1 (July 1993) - Horimoto, N; Koyanagi, T; Maeda, H; Satoh, S; Takashima, T; Minami, T; Nakano, H
Abstract : Fetal behavioural patterns were examined to test whether they could be used to localise sites of brain damage antenatally. Decreased fetal movement, persistent nonreactive fetal heart rate (FHR) pattern, and/or central nervous system malformation were used as indicators of possible neurological impairment. Ten fetuses tested in this way underwent further ultrasound examination observing movement of the extremities, chest wall (breathing), and eye and mouth, and active/quiet FHR patterns. Eight of these 10 fetuses were found on postnatal examination to have a brain impairment. The fetuses having potential in utero brain impairment were divided into four groups: those with (1) lesion sites at, or caudal to, the pons-medulla that were specifically identified by fetal behaviour, (2) diffuse lesions in the brain which, although resulting in abnormal behaviour, could not be localised by this behaviour, (3) lesions localised in the cerebral hemisphere(s) but with no abnormal behaviour and (4) temporally abnormal behaviour in utero, finally changing over to a normal pattern with no neonatal neurological abnormality. A screening system for the antenatal assessment of brain impairment is thus proposed.